Pengaruh Technological Pedagogical Content Knowledge (TPACK) terhadap Hasil Belajar IPS pada Siswa Kelas V - Rini, Dista Puspita; Praptiningsih, Dra; Kurnianto, Bagas (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2023)
The use of technology in learning is a concrete form of building education in the 21st century. This study aims to determine the Technological Pedagogical Content Knowlegde (TPACK) on social studies learning outcomes in fifth grade students at Wonoyoso State Elementary School, Semarang Regency. The research used quantitative and model used is Quasi Experimental Design with the research design used The Nonequivalent Control Group Design. Experimental class students totaled 28 students, while control class students totaled 28 students. The sample was selected by Purposive Sampling with a sample size of 56 students. The data collection technique used in this study was a test technique to measure the social studies learning outcomes of fifth grade students. The results showed that Technological Pedagogical Content Knowlegde (TPACK) affects the social studies learning outcomes of fifth grade students of Wonoyoso Elementary School. This is evidenced by the acquisition of hypothesis testing results with the T test formula, namely with the value of T count greater than T table (9.9123 > 2.670) then Ha is accepted and Ho is rejected. This means there is an influence of Technological Pedagogical Content Knowlegde (TPACK) on social studies learning outcomes in fifth grade students at Wonoyoso Elementary SchoolKeywords: TPACK, learning outcomes, social studies